1954
DOI: 10.1172/jci102928
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Negative Pressure Breathing on Water and Electrolyte Excretion by the Human Kidney

Abstract: The effects of decreased intrathoracic pressure on arterial blood pressure (1), venous pressure (2, 3), cardiac output (4), and pulmonary pressure and volume (5) have been investigated in the past. The present study was prompted by the association of marked diuresis with continuous negative pressure breathing in anesthetized animals (6) and the observation that in unanesthetized man continuous positive pressure breathing leads to an oliguria (7). The purpose of this investigation was to demonstrate that human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1955
1955
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The results of this study confirm earlier demonstrations of the alterations in urine flow that are associated with changes in intrathoracic pressure (1)(2)(3)(11)(12)(13). Although earlier reports suggested that water excretion was altered independent of electrolyte excretion and unrelated to changes in renal hemodynamics, these two factors were not completely evaluated.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results of this study confirm earlier demonstrations of the alterations in urine flow that are associated with changes in intrathoracic pressure (1)(2)(3)(11)(12)(13). Although earlier reports suggested that water excretion was altered independent of electrolyte excretion and unrelated to changes in renal hemodynamics, these two factors were not completely evaluated.…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested in earlier reports that the intrathoracic portion of the cardiovascular system contains a volume receptor area (1,3). Further study has demonstrated that the left atrium is one such receptor area (4,5).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations